Recovery of Heavy Metals from Eletroplating Rinse Wastewater by Reverse Osmosis - See, Boon Yan (1996)
Electroplating rinse wastewater contains a number of toxic metals which are harmful to receiving waters. The Tubular B 1 Module (PCI Membrane Systems) with AFC 99 polyamide membrane was used to treat the aluminium anodizing rinse water at different feedwater concentrations and diff erent transmembrane pressures. Penneate flux was found to be directly proportional to transmembrane pressure and indirectly proportional to natural logarithms of feedwater concentrations. Aluminium concentration was reduced from 747.1 mg/l to 2. rejection at 65 bar transmembrane pressure and 40°C feedwater temperature. Overall conductivity rejection was in excess of 9 8% at 65 bar. Rejection efficiency was increased with increasing transmembrane pressure. However, permeate quality deteriorated with increasing feedwater concentrations. High production rate was recorded with 3.3 m3/m2.d at 7% recovery and 65 bar transmembrane pressure with a feedwater concentration of approximately 9,500 mg/l TDS (Total Dissolved Solids). Reverse osmosis penneate is suitable for reuse as rinse water in the factory. No membrane fouling was encountered during the study. Reverse osmosis was found to be an effective alternative for recovery of rinse water and heavy metals from the waste effluent compared to other conventional treatment technologies